Influence of hybrid energy storage systems on future microgrids - Mohamed Faisal Mohamed Soffe (2017)
The Hybrid Energy Storage System (HESS) has contributed greatly in the power industry as scientists and engineers looked towards renewable energy sources. The HESS will play a bigger role in the future of microgrids as more consumers switched to renewable energy sources. This alternative source to coal and oil will help reduce the global carbon footprints. However, the use of renewable energy sources can cause intermittent power interruptions as environmental changes are often unpredictable. Thus this can affect the reliability of the power system. The HESS then provides a solution to this limitation as it enhances the overall reliability, efficiency and safety of the power system.